GESTIÓN Y COMPETITIVIDAD EN LA ERA DE LA GLOBALIZACIÓN 1 - Bouby Tolentino, Francisca (2007)
The objective of this work is to carry out an analysis to manage the new era of the changing capitalist system, characterized by the full validity of the market economy and the quick globalization. To manage a country in development is different from managing a developed country. The globalization of the productive systems, allows the classification of the different countries in the world according to the relative weight of its respective work forces, depending, fundamentally on the world level competitiveness that these forces have. On this base it is considered that in the developing countries that integrate the First World, most of the labor force has the appropriate competitiveness level with the international standards. On the other hand, the Latin American countries in development as well as the Oriental Asia and the old Soviet world that conform the Third World, will not be able to absorb most of the labor force that come from the rural and informal economic sector. This position is reinforced in the fact that the levels of international competitiveness rise continually according to the advance of the technology.